A gluteal mass of Langerhans cell histiocytosis mimicking malignancy - Ibrahim, Z.A.; Lung, W.S; long, P.K. (Malaysian Journal of Medical Sciences, 2009)
Langerhans cell histiocytosis is a disease primarily affects the bone. More than 50 percent of the disease occurs between the age of 1 and 15. We reported a case of a 2 year old boy who presented with a gluteal mass. Radiographic imaging showed an osteolytic lesion suspicious of malignancy. However, the histological diagnosis was Langerhans cell histiocytosis.